Pengembangan Media Pembelajaran Berbasis Sparkol VideoScribe Pada Materi SPLTV di SMA Negeri 1 Suwawa - Juriah Aminuddin; Tedy Machmud; Bertu Rianto Takaendengan (FARABI: Jurnal Matematika dan Pendidikan Matematika, 2024)
The use of learning media is still limited, making students tend to be more passive during the learning process. At SMA Negeri 1 Suwawa, the learning process predominantly uses textbooks, whiteboards, LKPD, and sometimes PowerPoint. These limitations make it difficult for students to understand the material, including mathematics lessons on the material of the System of Linear Equations of Three Variables (SPLTV) which requires image visualization. With the existing problems, research was conducted by utilizing technology which aims to develop mathematics learning media using the Sparkol VideoScribe application on SPLTV material which was carried out involving 20 class X students at SMA Negeri 1 Suwawa in June. This type of research uses the Research and Development (R&D) method using the four-D development model, namely Define, Design, Develop and Disseminate. Data analysis was carried out based on expert assessments, teachers, and student responses using a Likert scale. The development assessment was carried out based on the results of three media validators as well as learning materials and obtained validation results of 77% for media and 82% for materials with criteria worth using. The results of teacher and student responses obtained an average total percentage of 98% and 85% respectively which indicates that the media used meets practical criteria. For further research, it can develop learning media that attract more students' attention in learning activities and increase the activeness of students in learning activities, especially math lessons on SPLTV material.